Studi Komparatif Variasi Ketebalan Pelat Baja ASTM A36 pada Main Steel sebagai Penopang Baterai - Rofiqah Sabila Hidayat Hidayat; Muhaji; Dedy Wahyudi; Ardan Nagra Coutsar; Dian Prasetyawati (Universitas Muhammadiyah Metro, 2026)
This simulation aims to conduct a comparative study of variations in the thickness of ASTM A36 steel plates to determine the most optimal thickness for supporting the load of batteries, which are currently a critical energy source. The analysis focuses on the values of von Mises stress, displacement, and safety factor. Battery supports are the primary focus of this study, which will compare variations in optimal thickness for batteries that typically require thicknesses of up to 3 to 4 mm; in this simulation, a thinner and optimal solution will be sought. As technology advances and the demands of manufacturing digitalization grow, production processes are increasingly utilizing simulations in Computer-Aided Engineering (CAE) software, making conventional testing more efficient. Using SolidWorks software simulation, a static analysis was conducted to evaluate each variation. ASTM A36 steel plates measuring 1400 mm in length, 70.6 mm in width, and with thicknesses of 1 mm, 2 mm, and 3 mm were selected to accommodate the battery weight. Three battery blocks, each weighing 5 kg, were used in this simulation. ASTM A36 material was selected because it has a high yield strength of 250 MPa. In addition to the parameters mentioned above, dynamic loads with variations of 1.5G and 2G will also be calculated. The optimal strength of the battery mount was determined through simulation in SolidWorks. The results of each thickness variation were then analyzed using a comparative study to determine the optimal thickness based on a comparison of von Mises stress, displacement, and safety factor. Ultimately, the optimal thickness was determined to be 3 mm, with von Mises stress reduced by 32.8% to 82 MPa. Displacement was reduced by 1.08% compared to the two previous variations, specifically 12 mm at the center of the plate. The optimal dynamic load stress occurs at a thickness of 3 mm.